The study of intestinal microbiota and duodenal aspirate in patients with giardiasis accompanied by allergic skin diseases - Pоkryshkо Olena; Kamyshnyi , Oleksandr; Tkachuk, Nataliya; Olyinyk , Nina; Petruk, Alina; Ivahiv, Oleh; Nychyk , Natalia; Pоkryshkо Alina (Annals of Mechnikov’s Institute, 2024)
Background. Giardia lamblia can be an etiological factor of allergic skin diseases. In the human body, giardia create parasitocenosis. Giardia’s colonization of the intestine causes dysbiosis throughout the gut that persists during infection, in turn affects the development of symptoms in patients with giardiasis. The purpose of the work was to study the duodenal aspirate and commensal gut microbiota in patients with giardiasis infestation, which was accompanied by allergic skin dermatoses. Materials and Methods. 38 patients with giardiasis accompanied by allergic skin diseases were examined. The presence of giardia in duodenal aspirates and stools samples was determined using light-optical microscopy and the method of polarized fluorescence. Microbiological studies of biological material were carried out in accordance with regulatory documents and generally accepted methods. Based on the results of the conducted microbiological study of the gut microbiota, the dysbiosis and its severity were determined according to the unified classification. Statistical processing was carried out using the Statistica 7.0 MicrosoftExel computer program. Results. The giardiasis was confirmed in all 38 examined persons. The efficiency of light optical microscopy of stool samples has been 55.3%, of duodenal aspirate samples - 71.5%. G. Giardia lamblia cysts were found in the fece samples of all patients. Vegetative forms of giardia were found in duodenal contents (55.5% of patients). Most often, trophozoites were found in portion C (26.7%). The efficiency of polarization fluorescence has been 92.1%. This method of Giardia detecting was more effective than light-optical microscopy by 20.6%. All patients were diagnosed with dysbiosis of gut. In most of them (86.4%) f subcompensated level of dysbiosis was found out. Among the microorganisms isolated from the duodenal aspirates, coagulase-negative cocci and yeast were dominated. Portion B of aspirates was the most contaminated with microorganisms, portion C was the least contaminated. Three-component microbial associations were dominated in a portion A; two-component associations – in a portion B. In a portion most of isolates were monocultures. Conclusions. G. lamblia cysts were found in stools of giardiasis patients with accompanying allergic skin diseases in 100.0% of cases, but only in 55.3% of people in the first sample. The efficiency of detecting G. lamblia in duodenal aspirate samples is 71.5%; moreover, vegetative forms of G. lamblia were found in 55.5%. There is a relationship between the presence of G. lamblia and the severity of intestinal dysbiosis. The results of the study showed that the presence of giardia can be an indicator of intestinal dysbiosis. G. lamblia is involved in the formation of a special state of parasitocenosis in the human body, which can include various bacteria and protozoa. Coagulase-negative staphylococci and Candida spp predominate in the microbial communities of duodenal contents. The colonization level of duodenal aspirates decreases according to the gradient: portion A → portion B → portion C. Treatment of patients with allergic dermatitis and giardiasis should be comprehensive, taking into account the intestinal dysbiosis diagnosed in them. Key words: Giardia lamblia, giardiasis, allergic skin diseases, laboratory diagnostics